Defensive team concept for slovak national team U16 - Torda, P.; Rozim, R.; Betak, B. (Acta Universitatis Matthiae Belii, Physical Education and Sport, 2011)
Significant task during writing this article is to introduce you, my concept and philosophy in developing team defense.. My main effort in coaching is to teach proper fundamentals in man-to-man defense and I believe after studying a lot of materials, discussions with very experienced coaches from my country and also from abroad and visiting coaching clinics and also major European championships the good aggressive defense can win the championship. Another point is that these principles and rules of individual technique and tactics in aggressive man-to-man defense can help to develop individual players and the whole team. A good aggressive man-to-man defense comes from very good learnt fundamentals and when players understand the fundamentals of the man-to-man defense it is very easy to teach them zones, zone presses etc. defenses.